2013
DOI: 10.1302/0301-620x.95b10.30204
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of the Mobility total ankle replacement at a mean of four years

Abstract: We performed a retrospective review of a consecutive series of 178 Mobility total ankle replacements (TARs) performed by three surgeons between January 2004 and June 2009, and analysed radiological parameters and clinical outcomes in a subgroup of 129 patients. The mean follow-up was 4 years (2 to 6.3). A total of ten revision procedures (5.6%) were undertaken. The mean Ankle Osteoarthritis Scale (AOS) pain score was 17 (0 to 88) and 86% of patients were clinically improved at follow-up. However, 18 patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 21 publications
0
6
1
Order By: Relevance
“…Despite the increased component accuracy and reproducibility that PSI may provide, concerns have been raised regarding the need for more periosteal stripping and soft tissue dissection compared with SR techniques in order to position the PSI guides correctly. The increased damage to the periosteum may impair local delivery of oxygen and nutrients, leading to ischemic necrosis with early and aggressive osteolysis, as described by multiple authors, including Koivu et al 19,20,[24][25][26]29 Our results do not support these concerns, with no statistical difference in rates of early osteolysis after TAA identified between the PSI (41%) and SR (36%) technique groups (P = .46). There was also no difference in the magnitude of osteolysis between the PSI and SR groups (P = .33) with only one lesion in each group being greater than 10 mm in diameter.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Despite the increased component accuracy and reproducibility that PSI may provide, concerns have been raised regarding the need for more periosteal stripping and soft tissue dissection compared with SR techniques in order to position the PSI guides correctly. The increased damage to the periosteum may impair local delivery of oxygen and nutrients, leading to ischemic necrosis with early and aggressive osteolysis, as described by multiple authors, including Koivu et al 19,20,[24][25][26]29 Our results do not support these concerns, with no statistical difference in rates of early osteolysis after TAA identified between the PSI (41%) and SR (36%) technique groups (P = .46). There was also no difference in the magnitude of osteolysis between the PSI and SR groups (P = .33) with only one lesion in each group being greater than 10 mm in diameter.…”
Section: Discussioncontrasting
confidence: 57%
“…In the Mobility TAA, osteolysis has been reported between 12% of patients at 3-year follow-up, to 29% at 4-year follow-up. [19][20][21] The Salto Talaris fixed bearing prosthesis has a reported incidence of osteolysis of 31% at 5.2 years 22 ; meanwhile the Hintegra total ankle replacement has 37% at 40.8 months. 23 Even considering the wide range in the reported incidence of osteolysis and aseptic loosening after TAA, it is well known that it occurs more frequently than when compared with total hip and knee arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Component malposition did not contribute to medial malleolar stress in this study, as no patient had a coronal component more than 2 degrees off the long axis of the tibia. Muir et al 24 also did not identify an association with component alignment and medial pain.…”
Section: Discussionmentioning
confidence: 91%
“…Postoperative pain has been reported in up to 40% of TAA patients. 14,15,24 There have been many etiologies described, including osteophyte development, stress fracture, implant failure/loosening, oversizing the tibial component, talar impingement against the malleolus, malleolar fracture, and adjacent joint arthritis. * As this study demonstrates, under conditions where a TAA patient presents with delayed-onset medial pain and radiographic examination is normal, it may be difficult to determine the exact cause of the pain.…”
Section: Discussionmentioning
confidence: 99%
“…Muir et al 20 reported a retrospective analysis of 129 Mobility ankle arthroplasties with a mean follow-up of 48 months. Rheumatoid arthritis was the indication for surgery in only 12% of the sample.…”
Section: Review Of Recent Prosthesis-specific Studiesmentioning
confidence: 99%